2013
DOI: 10.1227/neu.0b013e318286fab3
|View full text |Cite
|
Sign up to set email alerts
|

Angular Remodeling in Single Stent-Assisted Coiling Displaces and Attenuates the Flow Impingement Zone at the Neck of Intracranial Bifurcation Aneurysms

Abstract: Stent-induced angular remodeling significantly altered bifurcation apex hemodynamics in a favorable direction by blunting apical pressure and inducing the narrowing and migration of the FIZ, a novel response to intracranial stenting that should be added to intimal hyperplasia and flow diversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 17 publications
(21 reference statements)
4
64
0
Order By: Relevance
“…Straightening the vascular bifurcation angle results in statistically significant migration of the flow impingement zone to the distal vessel as well as narrowing its width which, in effect, fundamentally alters the underlying wall shear stress and decreases the pressure at the bifurcation (4,5). Additionally, it is known that, the flow vortices at the arterial bifurcation tend to be larger if the combined size of the distal vessels is much larger than the parent artery or if the bifurcation angle is large (2).…”
Section: Discussionmentioning
confidence: 99%
“…Straightening the vascular bifurcation angle results in statistically significant migration of the flow impingement zone to the distal vessel as well as narrowing its width which, in effect, fundamentally alters the underlying wall shear stress and decreases the pressure at the bifurcation (4,5). Additionally, it is known that, the flow vortices at the arterial bifurcation tend to be larger if the combined size of the distal vessels is much larger than the parent artery or if the bifurcation angle is large (2).…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have shown that straightening of vessels may reduce recanalization rates [3,4,12]. Because there was no difference in straightening effects between the Enterprise and Enterprise 2 stents, this strategy would not change between these stents.…”
Section: Discussionmentioning
confidence: 99%
“…Several reasons may account for the improved durability of treatment with self-expanding stents: denser aneurysm packing with increased neck coverage, flow diversion, parent vessel straightening, angular remodeling, and fibroelastic tissue formation along the neck of the aneurysm. 3,4,6,8,11,14,18,23 Likewise, the use of the balloon remodeling technique was found to significantly improve the durability of endovascular therapy. 3,7 The strong association between delayed aneurysm recurrence and male sex is interesting and has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%